Long-Lived Plasma Cells Are Contained within the CD19(-)CD38(hi)CD138(+) Subset in Human Bone Marrow - Halliley, Jessica L; Tipton, Christopher M; Liesveld, Jane; Rosenberg, Alexander F; Darce, Jaime; Gregoretti, Ivan V; Popova, Lana; Kaminiski, Denise; Fucile, Christopher F; Albizua, Igor; Kyu, Shuya; Chiang, Kuang-Yueh; et al. (Immunity (Cambridge, Mass.), 2015)
Antibody responses to viral infections are sustained for decades by long-lived plasma cells (LLPCs). However, LLPCs have yet to be characterized in humans. Here we used CD19, CD38, and CD138 to identify four PC subsets in human bone marrow (BM). We found that the CD19(-)CD38(hi)CD138(+) subset was morphologically distinct, differentially expressed PC-associated genes, and exclusively contained PCs specific for viral antigens to which the subjects had not been exposed for more than 40 years. Protein sequences of measles- and mumps-specific circulating antibodies were encoded for by CD19(-)CD38(hi)CD138(+) PCs in the BM. Finally, we found that CD19(-)CD38(hi)CD138(+) PCs had a distinct RNA transcriptome signature and human immunoglobulin heavy chain (VH) repertoire that was relatively uncoupled from other BM PC subsets and probably represents the B cell response's "historical record" of antigenic exposure. Thus, our studies define human LLPCs and provide a mechanism for the life-long maintenance of anti-viral antibodies in the serum.